2009
DOI: 10.1172/jci38619
|View full text |Cite
|
Sign up to set email alerts
|

Protein degradation in Parkinson disease revisited: it’s complex

Abstract: Parkinson disease (PD) is the second most common neurodegenerative disorder, and mutations in the genes PTEN-induced putative kinase 1 (PINK1, also known as Parkinson disease 6 [PARK6]), PARKIN (also known as PARK2), and DJ-1 (also known as PARK7) cause autosomal recessive forms of PD/parkinsonism. PINK1 encodes a protein with a mitochondrial targeting sequence and a putative serine/threonine kinase domain, and PINK1 is predominantly localized to mitochondria (1). The Parkin protein contains two RING finger mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 34 publications
1
18
0
3
Order By: Relevance
“…Moreover, a dysfunctional proteo-somal degradation pathway (Fig. 1A and C) has been suggested to be involved in the neurodegenerative process of PD and mercury neurotoxicity (Li and Guo, 2009;Lim and Tan, 2007;Yu et al, 2010). Our results confirmed that the ubiquitin-proteasome system was a common target affected by both MeHg and MPP + treatments.…”
Section: Discussionsupporting
confidence: 82%
“…Moreover, a dysfunctional proteo-somal degradation pathway (Fig. 1A and C) has been suggested to be involved in the neurodegenerative process of PD and mercury neurotoxicity (Li and Guo, 2009;Lim and Tan, 2007;Yu et al, 2010). Our results confirmed that the ubiquitin-proteasome system was a common target affected by both MeHg and MPP + treatments.…”
Section: Discussionsupporting
confidence: 82%
“…Negative and positive t values indicate depletion and enrichment of the feature in the test set, respectively. ͓T͔ [5][6][7][8][9][10] and ͓TA͔ 3-6 are binding motifs for the poly(A)-binding proteins Pub1 and Pab1, respectively (54). AUC, area under curve (where the curve is the receiver-operator characteristic), the closer to 1 the better is the prediction; PARS, parallel analysis of RNA structure, i.e.…”
Section: Table II Characteristics Of the Three Largest Clustersmentioning
confidence: 99%
“…son's disease (6), and cardiovascular disease (7). Moreover, protein aggregation is related to the impairment of the ubiquitin proteasome system, and both processes are hallmarks of several neurodegenerative diseases (8,9).…”
mentioning
confidence: 99%
“…A handful of substrates have been identified, including Parkin itself and CDCrel-1, synphilin-1, Pael-R, glycosylated ␣-synuclein, FBP1 (far upstream elementbinding protein 1), and the RNA-processing protein subunit p38/AIMP2 (16 -19). A putative mechanism by which mutations of Parkin cause PD would be abnormal accumulation and aggregation of the above substrates due to insufficient E3 ligase activity for ubiquitin-proteasome-dependent protein turnover (18,20,21). Surprisingly, only p38/AIMP2 and FBP1 were found to be accumulated in the brain samples of PD patients or in Parkin knock-out mice (16,17,19).…”
mentioning
confidence: 99%